Factors influencing the decision to adopt an Information Technology Risk Management framework at universities in South Africa - Seale, Tina (Department of Information Systems, 2017)
The purpose of this research is to identify the main factors influencing universities in South Africa to adopt specific Information Technology Risk Management (ITRM) frameworks. The research has been conducted to understand why universities adopt different ITRM frameworks. The sample group of universities used in this research comprise four public universities in the Western Cape, South Africa. To gain further insights into the decision-making process, an interpretivist philosophy, using a deductive approach, has been used. Roger's Diffusion of Innovation theory is used as a lens to understand the decision-making process to adopt an ITRM framework at universities. A combination of questionnaires, interviews and secondary data has been used to collect data from the sample of universities. The findings establish that inconsistent ITRM frameworks have been adopted at the participating universities. Numerous factors, both internal and external to the university, influence the decision-making process. Internal factors which have had a strong influence on the adoption of an ITRM encompass the attitude of decision makers, strong corporate governance and strong leadership in top management and within the IT department. External factors with the strongest influence on the decision-making process are contained within the legislative and statutory requirements mandated by the Higher Education Act 101 of 1997. Additional external factors influencing choice are certain regulatory requirements as well as the perceived popularity of certain frameworks. The recommendation of external parties is often closely considered when determining framework fit and adaptability to a university's environment. The sample group of universities has been limited to four public universities within the Western Cape. As a consequence, the data collected is limited due to minimal participation across all participating universities. Further research, such as case studies, is recommended in order to gain additional in-depth knowledge of the decision-making process regarding the implementation of ITRM frameworks at universities.